Story to Improve Language Abilities of Early Children - Hibana Hibana; Susilo Surahman; Muthia Rahman Nayla (JOYCED: Journal of Early Childhood Education, 2021)
Language skills in PAUD Terpadu Mutiara Yogyakarta children are still low. This matter is caused by less attractive and varied educational procedures and media. The use of exciting techniques such as telling is expected to improve children's language skills. This research aims: to identify the skills in telling children in improving the language skills of children PAUD Terpadu Mutiara Yogyakarta; to recognize the increase in language skills of children in PAUD Terpadu Mutiara Yogyakarta through telling. This research's procedure involves action research, which consists of 2 cycles, the first cycle of 8 actions and the second cycle of 3 steps. The study subjects were children in group B, with 16 children consisting of 5 boys and 11 girls. Methods of collecting information through observation, interviews, and documentation. The method of information analysis was tried descriptively, qualitatively, and quantitatively. The action's success criterion is if the average class score in improving language skills reaches 75%. The research results show that: the media implementation process includes three stages, namely preparation, implementation of activities, and assessment; in Cycle I, it increased from the results of pre-action by 27% to 36%, and in Cycle II, it increased to 75%. So it can be concluded that the implementation of telling can improve PAUD Terpadu Mutiara Yogyakarta children's language skills.